Preparation of different zinc compounds from a smithsonite ore through ammonia leaching and subsequent heat treatment - Ehsani, Arman; Ehsani, İlhan; Obut, Abdullah (Oficyna Wydawnicza Politechniki Wroclawskiej, 2021)
In this study, firstly, the effects of ammonia concentration, leaching time and solid/liquid ratio on the leaching behaviour of zinc from a smithsonite (ZnCO3) ore sample in aqueous ammonia solutions were investigated at room temperature by chemical, X-ray diffraction (XRD) and Fourier-transform infrared (FT-IR) spectroscopy analyses. It was found that leaching ratio of zinc steeply increased from 30.1 to 76.2% with increasing ammonia concentration from 1.0 to 4.0 M and maximum zinc leaching ratio of 79.7% was reached after leaching in 13.3 M NH3 solution. The XRD pattern of the residue obtained after leaching in 4.0 M NH3 solution for 90 min at solid/liquid ratio of 0.15 g/mL, the optimum condition, showed that smithsonite phase in the ore sample almost completely dissolved whereas the gangue minerals goethite and calcite remained unaffected, confirming the selectivity of ammonia solution for zinc dissolution. Together with zinc, leaching ratios of cadmium were also determined. In second part of the study, precipitation tests (by complete drying at different temperatures) were conducted on dissolved zinc, carbonate and ammonia containing pregnant solutions obtained after selected leaching experiments. By complete drying of the pregnant solutions at low temperatures, i.e. 50°C, relatively pure solid zinc ammine carbonate (Zn(NH3)CO3) precipitates and at higher temperatures, i.e. 150°C, quite pure solid zinc carbonate hydroxide (Zn5(CO3)2(OH)6) precipitates could be prepared. High-temperature heating of Zn(NH3)CO3 and Zn5(CO3)2(OH)6 precipitates at 450°C yielded single-phase zinc oxide (ZnO). The chemical compositions, FT-IR spectra and scanning electron microscope (SEM) photographs of some of the precipitates were also presented.
Keywords: Ammonia leaching; Smithsonite; Zinc ammine carbonate; Zinc carbonate hydroxide; Zinc oxide